THE DELIBERATIVE GOVERNANCE IN LABOUR POLICY INNOVATION, EVIDENCE FROM REGIONAL GOVERNMENT OF CENTRAL JAVA PROVINCE: EVIDENCE FROM REGIONAL GOVERNMENT OF CENTRAL JAVA PROVINCE - Tasroh Tasroh; Paulus Israwan Setyoko; Tobirin Tobirin (Natapraja, 2026)
This study aims to explore how deliberative governance plays a significant role in improving the quality of labour policy innovation, especially in the Central Java region. Applying descriptive methods through in-depth interviews, policy studies, and observations of 100 relevant key-informants, it can be concluded that deliberation in term of labour policy innovation could facilitate and provide a structured platform for dialogue among the government (executive and legislative), labour unions, employer associations, NGOs, and experts. By enhanching labour participation could reduces resistance, enacting inclusiveness and increases the legitimacy of policies. Labour policies are more likely to be accepted and implemented effectively if executives, legislatives, workers, corporates, and civil society feel ownership of the process. However, there are still many weaknesses in its practice that tend to lead to pseudo-participation where the presence of actors is not fully independent because there is still  dominance of elite actors who ultimately control the decision.